2013
DOI: 10.2298/aci1302053m
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of the unstable type C pelvic injury

Abstract: Rotationally and vertically unstable injuries to the pelvic ring (Type C) require stabilisation of the anterior and posterior pelvic ring complex. Inadequate treatment of these injuries leads to chronic instability of the pelvic ring, which can finally cause permanent disability. Open reduction and stable internal fixation of the anterior and posterior complex of unstable pelvic ring injuries are standard procedures in the treatment of hemodynamically stable patients with (Type C) pelvic injuries. Our aim is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Posterior pelvic ring disruption remains a challenging problem for orthopaedic surgeons. The major surgical aim of posterior pelvic ring disruption is to promote the recovery of postoperative biomechanics of the posterior pelvic ring. Therefore, the more that postoperative pelvic stress can approximate its natural stress, the better the clinical efficiency that can be achieved by an internal fixation system.…”
Section: Discussionmentioning
confidence: 99%
“…Posterior pelvic ring disruption remains a challenging problem for orthopaedic surgeons. The major surgical aim of posterior pelvic ring disruption is to promote the recovery of postoperative biomechanics of the posterior pelvic ring. Therefore, the more that postoperative pelvic stress can approximate its natural stress, the better the clinical efficiency that can be achieved by an internal fixation system.…”
Section: Discussionmentioning
confidence: 99%
“…Kellam et al report that women usually complain of dyspareunia after lateral compression injuries [15]. Oliver et al found that 31% of female patients from their study sample had dyspareunia but this did not [17]. In our series of first 26 patients the average Majeed score was 72.1.…”
Section: Discussionmentioning
confidence: 51%
“…Due to all these facts, it can be considered that these injuries need to be treated in highly specialized institutions using a multidisciplinary team approach. In hemodynam-ically stable patients, the method of choice is the definitive fixation of anterior or both anterior and posterior pelvic ring complex (type B and C injuries) (6,37). Definitive stabilization of the pelvic ring should be obtained as early as possible, preferably within the first seven days after the initial trauma (4).…”
Section: Discussionmentioning
confidence: 99%
“…Fixation of pelvic ring in emergencies is generally temporary and it is achieved with external fixation or by pelvic C clamps (4,5). After stabilization of the general health status, it is necessary to perform a stable pelvic ring fixation and restore the patient to prehospital activity (6).…”
Section: Introductionmentioning
confidence: 99%